(untitled) - Bracewell, Ron (New York, 1965)
Transform methods provide a unifying mathematical approach to the study of electrical networks, devices for energy conversion and control, antennas, and other components of electrical systems, as well as to complete linear systems whether electrical or not.
Keywords: Fourier analysis,Mathematical analysis,Phân tích Fourier,Phân tích toán học